An anomalous neural interconnection between the Lingual and Mylohyoid Nerves - Khizer Hussain Afroze M; Sangeeta M; Pagutharivu P (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT The interconnection between the lingual nerve (LN) and the hypoglossal nerve, the LN and the inferior alveolar nerve (IAN), and the LN and the mylohyoid nerve (MHN) has already been documented in the literature. Despite the fact that variations in the course of the MHN in regard to the mandible are regularly observed, they have yet to be well documented in the anatomical or surgical literature. This anatomical variety necessitates that surgeons and anesthesiologists who routinely perform oro-surgical interventions and nerve blocks in the face for various neuralgias enhance their knowledge and awareness in order to avoid unintended nerve injury. In the present case report, we observed an aberrant neural loop connecting LN and MHN, as well as anatomical insight into an integrated component of MH along with LN in addition to the motor component.Keywords : Lingual nerve, Mylohyoid nerve, Interconnection, Neural Loop Correspondence drafroze.homoeo@gmail.com